Sistema prisional brasileiro no século XXI: segregação social e criminalização da pobreza - Santos, Raquel dos (2020)
This research deals with the history of Brazilian prisons as a space for social segregation and criminalization of poverty, aiming to reveal the functionality of prisons in capitalist society as an instrument of social control, repression and surveillance of marginalized “subaltern classes”, refunctionalized in the context of the State neoliberal. The study was carried out through bibliographic and documentary research, using as theoretical reference authors such as Marx, Engles, Wacquant, Melossi, Pavarini, Lemos, Torres and Pastana, among others, in order to understand the correction houses, since the accumulation process primitive to modern prisons, such as deprivation of liberty, criminal control of the state for surveillance, containment of marginalized people, functional for reproducing social inequalities and maintaining capital. Since its inception, prison has been a coercive instrument of the State and functions as a supposed solution to the problem of crime and misery. This phenomenon is present mainly in countries with dependent capitalism such as Brazil, which occupies the third position in the ranking in mass incarceration in the world, behind only the United States and China. The prison is considered a contradictory institution that develops along with the formation of the capitalist system and sharpens its intervention with the advancement of this mode of production, particularly concentrated on the poor population “deviant” from the social order that committed crimes against private property, life and linked to drug trafficking. The problem of incarceration is the reverse of the neoliberal model, marked by class, race and territory. This selective and punitive wave is now consolidated by a contradictory and exclusive criminal policy, in which the intensification of the repressive force of the State falls on the marginalized poor population. The prison proves to be functional to the bourgeois order, hence the need to think of a society without prison to end the state of barbarism in prison.